2010
DOI: 10.1007/s11154-010-9149-x
|View full text |Cite
|
Sign up to set email alerts
|

Permanent neonatal diabetes due to activating mutations in ABCC8 and KCNJ11

Abstract: The ATP-sensitive potassium (K(ATP)) channel is composed of two subunits SUR1 and Kir6.2. The channel is key for glucose stimulated insulin release from the pancreatic beta cell. Activating mutations have been identified in the genes encoding these subunits, ABCC8 and KCNJ11, and account for approximately 40% of permanent neonatal diabetes cases. The majority of patients with a K(ATP) mutation present with isolated diabetes however some have presented with the Developmental delay, Epilepsy and Neonatal Diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 61 publications
1
74
0
1
Order By: Relevance
“…Therefore, they have an overactive channel that remains opened, either increasing the K ATP activity mediated by Mg nucleotides or altering the intrinsic gating (Edghill et al, 2010;Remedi and Koster, 2010). Gloyn et al (2004) reported genetic variants in Kir6.2 as the potential cause of NDM for the first time in 2004.…”
Section: Pancreatic K Atp Channelopathiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, they have an overactive channel that remains opened, either increasing the K ATP activity mediated by Mg nucleotides or altering the intrinsic gating (Edghill et al, 2010;Remedi and Koster, 2010). Gloyn et al (2004) reported genetic variants in Kir6.2 as the potential cause of NDM for the first time in 2004.…”
Section: Pancreatic K Atp Channelopathiesmentioning
confidence: 99%
“…In addition, variants of Val59, Cys166, Ile197, and Ile296 residues involved in the channel gating impair the open probability of the channel (Proks et al, 2005;Edghill et al, 2010). SUR1 mutations affect either the Mg-nucleotide-mediated activation or the intrinsic gating.…”
Section: Pancreatic K Atp Channelopathiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Olguların çoğunun SUR1 (ABCC8) genindeki mutasyonlardan kaynaklandığı bildirilmiş ve bugüne kadar 150'den fazla mutasyon tespit edilmiştir (9,10) . Daha az oranda ise Kir.…”
Section: Discussionunclassified
“…Many of these genes have also been described in other disorders of insulin secretion, namely neonatal diabetes or congenital hyperinsulinism [43][44][45][46]. MODY 2 (GCK) and MODY 3 (HNF1A) account for the majority of MODY [18,20].…”
Section: Subtypes Of Modymentioning
confidence: 99%